First Experience of Inserting a Metallic Mesh Stent (Uventa Stent) in Malignant Ureteral Obstruction in Iran - Ghaed, Mohammad Ali; Daniali, Maziar; Ebrahimian, Mohammad (Urology Journal, 2018)
Malignant ureteral obstruction is usually caused by an extrinsic compression including intra-abdominal cancers. One of the treatment modalities decompressing the obstruction is applying stent to open the ureter. Metallic Stent is an effective instrument which we used for the first time in Iran in our patient who had a metastatic colon cancer with a single kidney and we used a Novel, Double-Layered, Coated, Self-expandable Metallic Mesh Stent (Uventa Stent) to keep the ureter open. After six months of follow up with ureteroscopy, there was no obstruction any more.